Reflecting on Media and Communication: Keynote and Plenary Perspectives from the Communication and Media Centre International Conference 2024 - COMETIC '24 - Mohamed, Shafizan (Communication and Media Centre (COMET), IIUM, 2025)
This monograph presents key insights and research findings from COMETIC ’24, an international conference themed Reflecting Values and Impacts. The conference provided a critical platform for scholars, practitioners, and students to examine the evolving role of media and communication in a rapidly changing global landscape. Addressing issues such as digital ethics, misinformation, artificial intelligence, and the cultural implications of technological advancements, the discussions emphasized the ethical, social, and policy dimensions of contemporary media practices. Through keynote speeches, panel sessions, and research presentations, COMETIC ’24 fostered dialogue between academia, industry, and institutions, promoting the integration of theoretical perspectives with real-world applications. This collection aims to contribute to the broader discourse on responsible and innovative media practices while inspiring future scholarship and ethical leadership in the field.